Diversifikasi Kurikulum dalam Kerangka Desentralisasi Pendidikan - Sutjipto -- (Jurnal Pendidikan dan Kebudayaan, 2015)
The purpose of this article is to examine curriculum development in the context of decentralized education governance. The results of the study show that, firstly, the legislation in effect contains provisions that make it possible for each district/region to play a role in developing curriculum tailored to the characteristics, needs and potential of each district/region. Second, diversifying and customizing curriculum content can begin with the formation of ideas and designs as well as the implementation and evaluation of the existing curriculum. Alterations made to curriculum content can range in scope from the structuring of the curriculum, the selection of essential study materials or the elaboration upon the existing standard. Third, there needs to be a change in the understanding of curriculum diversification and development. Such development should be understood as intricate work that requires professionals and experts to work together as a team to be more adequate, efficient and effective. Fourth, in terms of human resources, regional areas in Indonesia are considered to have people who are experienced in developing and customizing curriculum. Fifth, diversification of the curriculum still requires a variety of regulations to form a basis from which the development team can carry out its duties. It can be concluded that policy that facilitates the customization of the curriculum has been enacted to encourage diversity, which evolves continuously without disregarding national education goals.ABSTRAK Tujuan artikel ini untuk mengkaji khasanah pengembangan diversifikasi kurikulum ditinjau dari domain desentralisasi pendidikan. Hasil kajian menunjukkan bahwa pertama, dari sisi peraturan perundang-undangan yang berlaku terdapat ketentuan yang mengikat semua pihak bahwa daerah dimungkinkan dapat berperan dalam pengembangan diversifikasi kurikulum yang disesuaikan dengan karakteristik, kebutuhan dan potensinya. Kedua, konten diversifikasi kurikulum dapat dimulai dari ide, perancangan, implementasi dan evaluasi kurikulum yang cakupannya mulai dari penataan struktur, pemilihan bahan kajian yang esensial baik secara utuh maupun merupakan penjabaran dari standar yang ada. Ketiga, dengan memandang bidang pekerjaan pengembangan diversifikasi kurikulum sebagai wilayah garapan yang tidak sederhana diperlukan tenaga pengembang yang profesional, yang berarti tim tidak mungkin bekerja sendiri agar tugas-tugas tim menjadi lebih memadai, efisien, dan efektif. Keempat, dari kesiapan sumber daya manusia daerah dianggap cukup berpengalaman dalam mengembangkan diversifikasi kurikulum. Kelima, bahwa diversifikasi kurikulum masih memerlukan beragam regulasi sebagai dasar bagi tim pengembang untuk melaksanakan tugasnya. Dengan demikian dapat disimpulkan bahwa diversifikasi kurikulum merupakan kebijakan yang telah diberlakukan untuk mendorong keberagaman berkembang secara terus menerus tanpa menafikan tujuan pendidikan nasional.